PENGARUH FLASH SALE DAN TESTIMONI TERHADAP KEPUTUSAN PEMBELIAN PADAE-COMMERCE SHOPEE - Ega Trivilia Rizki, (2023)
Due to the development of technology, it is easy for consumers to fulfill their needs. In fact, coming directly to a shop can now be replaced by simply clicking on a smartphone. One of the positive benefits resulting from the current system is the emergence of e-commerce. In Indonesia, e-commerce has started to appear with their respective diversity, one of which is Shopee. The purpose of this study is to determine the effect of flash sales and testimonials on purchasing decisions. This research is a quantitative research which data were obtained through a questionnaire and measured using a Likert scale using the Partial Least Square (PLS) method processed using Smart PLS3.3.3. There is a total of 100 respondents used as the sample, and purposive sampling method is used as the sampling technique. The results of this study indicate that the flash sale variable has a positive and significant effect on purchasing decisions of 0.444 and testimonials have a positive effect on purchasing decisions of 0.524. The three variables in this study have a coefficient of determination of 0.829 or 82.9% in influencing purchasing decisions on Shopee.